Anogenital warts – the new treatment options - Joanna Salomon; Jacek Szepietowski (Przegląd Dermatologiczny, 2014)
Anogenital warts are hyperproliferating skin changes resulting from human papilloma virus (HPV) infection. This is the most common clinical manifestation of this infection. In over 95% of cases, HPV types 6 and 11 are isolated from the lesions, which are not regarded to be oncogenic types, but in some patients coexistence of oncogenic types of HPV is observed. There are many treatment modalities that are used to treat anogenital warts, but none of them prevents relapses. The available therapeutic methods may be used by the patient at home or may be performed in outpatient care units. The home options are podophyllotoxin, imiquimod and sinecatechin. Sinecatechin, the newest topical agent, is an antioxidant with antiproliferative, immunomodulatory, antiviral and anticancer properties. The efficacy of sinecatechin was proved in three randomized clinical trials with a large number of patients. The reported recurrence rate was very low. The tolerance of the treatment was reported to be very good. In Poland an ointment with 10% sinecatechin extract is registered. The preparation should be applied three times daily, until complete resolution of skin changes. The duration of treatment may last up to 16 weeks. The ambulatory care treatment options are cryotherapy, trichloroacetic acid application and surgical methods.